The ASSOCIATION OF DEMOGRAPHIC VARIABLES WITH EARLY RECOVERY AFTER CORONARY ARTERY BYPASS GRAFTING AT CARDIAC CARE PUBLIC HOSPITAL, KARACHI. - Khan, Ameer Ullah; Khan, Erum; Ghaffar, Almas; Ali, Muzafar (Journal of Liaquat University of Medical & Health Sciences, 2021)
Objective: To determine the association of demographic variables with postoperative early recovery in patients undergoing Coronary Artery Bypass Grafting. Methodology: A descriptive cross-sectional study was conductedat a cardiac care public hospital, Karachi, Pakistan from October 2019 to June 2020, recruiting 225 isolated Coronary Artery Bypass Grafting patients, not having a previous history of any cardiac surgery, combine surgeries, or history of mental disorder and other serious comorbid were included, using a non-probability consecutive sampling technique. Data were analyzed using the SPSS (version 23). Mean±SD and median (IQR) were computed for quantitative variables as appropriate while frequency and percentages for qualitative variables. Spearman’s correlation and logistic regression analysis were used to identify the association. The p-value of <0.05 considered as significant. Results: The mean age of participants was 55.13±8.02, majority of the participants were male (80%), of age <60 years (77.3%), belonged to the lower-middle class (81.3%), non-smokers (74.7%), and had normal hospital stay (61.8%). Gender, socioeconomic status, and preoperative status were significantly associated with postoperative recovery; age >60 years, HbA1C level, and preoperative status had a significant relationship with the length of ICU stay, and age >60 years, preoperative status, length of ICU stay and postoperative score were found in association with length of stay in hospital. Conclusion: Gender, older age, socioeconomic status, diabetes control, and preoperative status had significant effects on postoperative recovery, length of stay in ICU and hospital after Coronary Artery Bypass Grafting. Keywords: Demographics, recovery, early recovery, postoperative recovery, surgery , coronary artery bypass.